Mapping Global Trends in Civic Disposition and Its Implicationas for Civic Education - Rizqi Marifatun; Iqbal Arpannudin; Muhammad Kamil Ridha (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2025)
Civic disposition is a fundamental component of civic competence, encompassing the attitudes, values, and cognitive practices that facilitate democratic participation. This study aims to analyze the trends, themes, and evolving trajectories of research on civic disposition, as well as its implications for improving civic education in the digital era. The research gap exists because few comprehensive mapping studies utilize both bibliometric and systematic review methods. This study employs a Systematic Literature Review (SLR) methodology, conforming to the PRISMA framework, in conjunction with bibliometric analysis sourced from the Scopus database. From the 336 identified documents, 12 essential articles were selected and analyzed using VOSviewer to illustrate keyword co-occurrence, author collaboration, and country affiliation networks. The findings indicate that research on civic disposition is limited and predominantly conducted in the United States, with emerging contributions from Indonesia. Three principal research clusters were delineated: (1) civic education and contentious issues, (2) teacher training amid global crises, and (3) the integration of civic disposition with civic knowledge and competencies. The findings suggest that civic education should encompass reflective, participatory, and value-centered pedagogies, grounded in Pancasila and enhanced by digital technology, to cultivate democratic and virtuous citizens capable of confronting the challenges of the 21st century.Keywords: civic disposition, civic education, bibliometric analysis, PRISMA, Pancasila